2019
DOI: 10.1038/s41598-019-51269-8
|View full text |Cite
|
Sign up to set email alerts
|

MC-SleepNet: Large-scale Sleep Stage Scoring in Mice by Deep Neural Networks

Abstract: Automated sleep stage scoring for mice is in high demand for sleep research, since manual scoring requires considerable human expertise and efforts. The existing automated scoring methods do not provide the scoring accuracy required for practical use. In addition, the performance of such methods has generally been evaluated using rather small-scale datasets, and their robustness against individual differences and noise has not been adequately verified. This research proposes a novel automated scoring method na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 22 publications
6
55
0
Order By: Relevance
“…In addition, power spectral analysis revealed that during the possibly sleeping state, there was a peak in the delta band (1–4 Hz, Fig. 6 B), presumably corresponding to the stage of non-rapid eye movement sleep, the predominant form of sleep in mice 42 , 43 . The other state, conversely, had higher power in the gamma frequency band (30–100 Hz, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, power spectral analysis revealed that during the possibly sleeping state, there was a peak in the delta band (1–4 Hz, Fig. 6 B), presumably corresponding to the stage of non-rapid eye movement sleep, the predominant form of sleep in mice 42 , 43 . The other state, conversely, had higher power in the gamma frequency band (30–100 Hz, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further examination with time–frequency analysis demonstrated that one state displayed increased power mostly in a low frequency range (Fig. 6 A), potentially corresponding to sleeping periods of the animal, which are characterized by cortical EEG of higher amplitudes than awake stages 42 , 43 . In addition, power spectral analysis revealed that during the possibly sleeping state, there was a peak in the delta band (1–4 Hz, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although deep learning approaches have shown recent success in automated sleep scoring in both human patients 61 and animal models 62 (with large datasets and promising results), we opted for a shallow-learning approach without dimensionality reduction, allowing for greater interpretability of the results. The knowledge that the algorithm is using features with known biological relevance makes these results easier to approach and understand by the medical and research communities.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies proposed deep neural networks that were trained end-to-end on raw input EEG and EMG signals. One of the earliest studies 34 was based on 22 years of EEG and EMG signals from mice and reported an improvement of sleep scoring accuracy with respect to classical approaches. The system contained a bidirectional long short-term memory (LSTM) module in the classifier head to model long-range non-linear correlations 35 , and the training also included a retraining scheme.…”
Section: Introductionmentioning
confidence: 99%